The Zealandia Switch: Ice age climate shifts viewed from Southern Hemisphere moraines. (1st April 2021) - Denton, George H.; Putnam, Aaron E.; Russell, Joellen L.; Barrell, David J.A.; Schaefer, Joerg M.; Kaplan, Michael R.; Strand, Peter D.
Abstract: Two fundamental questions about the ice-age climate system await satisfactory resolution. First, if summer solar radiation intensity truly controls the orbital signature of the last glacial cycle, then why were major climatic shifts, including the last termination, globally synchronous? Second, what caused the millennial-scale climate oscillations superimposed on this cycle? We address these questions from a Southern Hemisphere perspective focused on mid-latitude mountain ice fields. We put particular emphasis on the last glacial termination, which involved both orbital-scale and millennial-scale climate elements and has generally well-resolved chronological control. Sustained retreat of mountain glaciers, documented by detailed mapping and chronology of glacial landforms in the Southern Alps and southern Andes, marked the termination of the last ice age, beginning ∼18 kyrs ago and involved a change from glacial to near-interglacial atmospheric temperature within a millennium or two. A rapid poleward shift of the Subtropical Front, delineating the northern margin of the Southern Ocean, ∼18 kyrs ago implies a concurrent poleward shift of the austral westerlies and leads us to hypothesize a southern origin for the dominant phase of the last glacial termination. Together with interhemispheric paleoclimate records and with results of coupled ocean-atmosphere climate modeling, these findings suggest a big, fast, and global end to the last ice age in which a southern-sourced warming episode linked the hemispheres. We posit that a shift in the Southern Ocean circulation and austral westerly wind system, tied to southern orbital forcing, caused this global warming episode by affecting the tropical heat engine and hence global climate. Central to this hypothesis, dubbed the 'Zealandia Switch', is the location of the Australia and Zealandia continents relative to Southern Hemisphere oceanic and atmospheric circulation. Coupled ocean-atmosphere climate modeling shows that the locus of the austral westerlies, whether in a more equatorward position representing a glacial-mode climate or in a poleward-shifted position marking interglacial-mode climate, has profound effects on oceanic and associated atmospheric linkages between the tropical Pacific and the Southern Ocean. Shifts in the austral westerlies have global climatic consequences, especially through resulting changes in the greenhouse gas content of the atmosphere and altered heat flux from the tropical Pacific into the Northern and Southern Hemispheres. We suggest that the last glacial termination was a global warming episode that led to extreme seasonality in northern latitudes by stimulating a flush of meltwater and icebergs into the North Atlantic from adjoining ice sheets. This fresh-water influx resulted in widespread North Atlantic sea ice that caused very cold boreal winters, thus amplifying the annual southward shift of the Intertropical Convergence Zone and the monsoonal rain belts. We further suggest that muted manifestations of the Zealandia Switch mechanism were responsible for smaller, recurring millennial-scale climate oscillations within the last glacial cycle. Highlights: Global synchrony of glacier moraine chronologies highlights Mercer's Paradox. Mechanisms of orbital forcing of climate re-assessed and new hypotheses presented. Orbital forcing of Southern Hemisphere circulation proposed to drive glacial cycles. Climate mode determined by continent/wind/ocean interactions: 'Zealandia Switch'. Southern driver suggested for millennial-scale climate shifts of the Last Glaciation.